the The Improvement of Fbg, Ang-1, VEGF, BDNF in Postoperative Patients with Brain Trauma Through Target Task Oriented Phrase Training: Fbg, Ang-1, VEGF, BDNF in Postoperative Patients - Liu, Bo (Journal of Medical Biochemistry, 2023)
Objective:It aims to explore the effect of target task oriented phase training on fibrinogen (Fbg), angiopoietin (Ang-1), vascular endothelial growth factor (VEGF), serum brain derived neurotrophic factor (BDNF) and quality of life in postoperative patients with brain trauma. Methods:142 patients with brain trauma who were operated in neurosurgery of our hospital from March 2020 to March 2023 are chosen and separated into two groups by random number table. The control group (n=71) receive routine postoperative training, and the experimental group (n=71) receive target task oriented training based on the control group, and the serum cell levels of nursing for 3, 7 and 14 days are compared. Improvement of limb function and quality of life after 2, 4, and 6 weeks of nursing care is observed. Results: Before nursing, the comparison in serum factor levels, limb function scores, and quality of life scores between the two groups was with P>0.05; After 3, 7, and 14 days of nursing, the Fbg of the control group was higher than that of the experimental group; The Ang-1, VEGF, and BDNF levels in the experimental group were higher than those in the control group (P
Keywords: Target task oriented phrase training; Postoperative brain trauma; Fbg, Ang-1, VEGF, BDNF; Quality of life